Endothelial Recovery in Bare Metal Stents and Drug-Eluting Stents on a Single-Cell Level. Issue 8 (24th June 2021) - Cornelissen, Anne; Guo, Liang; Fernandez, Raquel; Kelly, Michael C.; Janifer, Christine; Kuntz, Salome; Sakamoto, Atsushi; Jinnouchi, Hiroyuki; Sato, Yu; Paek, Ka Hyun; Kolodgie, Frank D.; Romero, Maria E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Healing processes, particularly reendothelialization, are essential for vascular homeostasis after plain old balloon angioplasty and stent implantation. Drug-eluting stents (DES) are commonly used for percutaneous coronary intervention because restenosis rates are reduced as compared with bare metal stents (BMS). However, in addition to understanding the nature of regenerated endothelial cells, concerns over incomplete stent healing persist, and the molecular effects of antiproliferative drug coatings on endothelium remain poorly understood. Approach and Results: We used the rabbit iliac artery model to analyze differences in stent endothelialization in BMS and DES. Histology and immunohistochemistry confirmed that stent coverage was significantly greater in BMS than in DES at 30 days after stent implantation. Single-cell RNA sequencing revealed a more immature transcriptomic signature of neointimal endothelial cell harvested from stented arteries in comparison with native and plain old balloon angioplasty–treated arteries. Whereas the genetic signature of BMS was overall proangiogenic with enrichment of genes involved in endothelial proliferation, sprouting, and migration, as well as extracellular matrix assembly, DES-derived endothelial cell showed upregulation of genes associated with angiogenesis inhibition and endothelial activation. Conclusions: Single-cell RNA sequencing analysis identified unique transcriptional changes within regenerated endothelium after plain old balloon angioplasty and stent implantation. These data suggest unique endothelial transcriptional differences, which characterize the different response of the endothelium to vascular injury and may help explain why long-term responses in DES remain suboptimal.